(untitled) (Revista cientifica In Vestigium Ire, 2021)
The use of renewable and non-renewable energy is often limited in rural areas or non-interconnected areas of Colombia. Hence, by having practical cases on photovoltaic systems for pumping water, they become energy solutions to improve the quality of life in these populations. In this article it can be observed how the use of solar energy represents a sustainable alternative for water pumping systems in rural areas of the country, as environmental impacts are reduced and environmental awareness is generated in the population. The use of solar energy compared to conventional energy reduces greenhouse gasemissions and ontributes to environmental sustainability, representing an alternative to generate environmental awareness against the use of alternative energy in order to provide energy solutions in the country. In the practical case carried out at the University of Córdoba - Colombia, the efficiency of the system in relation to solar brightness and the power of the pump can be analyzed to guarantee the water pumping system.